ANALISIS SISTEM AKUNTANSI PENERIMAAN KAS: STUDI KASUS PT. KAI DIVRE I SUMATERA UTARA - Hasibuan, Jihan; Siregar, Saparuddin (Jurnal Ekonomi STIEP, 2023)
The money receipt system is one of the trusted accounting systems that every business must have for accounting needs. Due to its availability, cash is one of the assets that significantly drives business growth. The purpose of this study is to provide an in-depth analysis of the revenue and cash accounting system of PT. KAI Divre I North Sumatra. North Sumatra cash receipt accounting system, operated by PT. KAI Regional Division I, is the subject of research. The findings revealed problems with the recognition of accounting information systems, delays in understanding that would also delay revenue recognition, inadequate placement of wrong people in proper jobs, lack of training for staff who could not use accounting information systems, and other problems.